Causes of diarrhea, pneumonia, and abortion in 1991 cattle submissions to the KSU Veterinary Diagnostic Laboratory - R.K. Frank; M.W. Vorhies; M. M. Chengappa (Kansas Agricultural Experiment Station Research Reports, 1992)
Causes of diarrhea, pneumonia, and abortion in Kansas cattle submissions to the Kansas State University Veterinary Diagnostic Laboratory during 1991 were summarized. Antimicrobial susceptibility results for Pasteurella haemolytica, Pasteurella multocida, Hemophilus somnus, and Salmonella spp., the common causes of pneumonia and/or diarrhea in cattle with increasing antibiotic resistance patterns, were also summarized. The most commonly diagnosed causes of diarrhea in young calves (under 1 month of age) were coronavirus, Escherichia coli, and Salmonella. The three most common causes of diarrhea in 1 to 18 month-old cattle were BVD virus, coccidia, and Salmonella. Most respiratory submissions were 7- to 18-month-old cattle. P. haemolytica and P. multocida were the most commonly identified pathogens from these cattle. In 20% of the cases, more than one pathogen was identified. The most commonly diagnosed cause of abortion was bacterial infection (20%), but a cause was not identified in nearly 70% of abortion submissions.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Disease; Diagnosis; Diarrhea; Pneumonia; Abortion